The diagnosis of lymphoproliferative diseases - Gatter, Kevin; Gatter, Kevin (John Wiley & Sons, 2011)
This highly illustrated, diagnostic guidebook provides a single comprehensive source of essential information to enable non-specialists to diagnose lymph node and related diseases with confidence. The text is didactic and practical, covering reactive as well as malignant conditions. Diagnosis of Lymphoproliferative Diseases approaches the disorders based on the WHO classification and is edited by members of the WHO panel for the classification of lymphomas. This second edition contains over 1000 high quality, digitised colour images and tables of essential criteria for each diagnosis. New feat.